(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
This study shows developing pavement quality concrete mixtures incorporating marble dust as partial replacement of cement as well as banana fiber. There is a growing interest in the construction of concrete pavements due to its high strength, durability, and better serviceability and overall economy in the long run. This study also shows that in view of the high flexural strength, high values of compressive strength and high values of split tensile strength, higher load carrying capacity and higher life expectancy, the combination of 10 to 15% marble dust replacement along with addition of 0.5 banana fiber is ideal for design of Pavement Quality Concrete (PQC). By replacing cement with marble dust and adding fibers it has been possible to achieve savings in cement. To produce thinner and green pavement sections of better quality, which can carry the heavy loads, is nowadays thrust.